SECOND WIND - Francis, Dick, 1920-2010, author 376665 (London : Pan Books, 2000)
Meteorologist Perry Stuart is offered a Caribbean hurricane-chasing ride in a small aeroplane as a holiday diversion. But he learns more secrets from the flight than wind speeds, and back home in England faces threats and dangers as deadly as anything nature can evolve.